Oral rehabilitation with fixed prosthesis - Watanabe Velásquez, Romel (2008)
This treatment was carried out in a 58 years old male patient, who has had the antecedent of a car crash accident two years before; he loosed several teeth and fractured others. Pulp necrosis and alteration of occlusal plane occurred. Because of the pathologies presented, it was installed a multidisciplinary treatment phase having periodontal, endodontic, surgical and orthodontic procedures, tehe installation of posts, crowns and fixed bridges. Treatment was carried out for five months.